Users and peers. From citizen science to P2P science - Alessandro Delfanti (JCOM: Journal of Science Communication, 2010)
This introduction presents the essays belonging to the JCOM special issue on User-led and peer-to-peer science. It also draws a first map of the main problems we need to investigate when we face this new and emerging phenomenon. Web tools are enacting and facilitating new ways for lay people to interact with scientists or to cooperate with each other, but cultural and political changes are also at play. What happens to expertise, knowledge production and relations between scientific institutions and society when lay people or non-scientists go online and engage in scientific activities? From science blogging and social networks to garage biology and open tools for user-led research, P2P science challenges many assumptions about public participation in scientific knowledge production. And it calls for a radical and perhaps new kind of openness of scientific practices towards society.